Perfil audiológico em policiais militares do Estado de São Paulo - Guida, Heraldo Lorena [UNESP]; Diniz, Thiago Hernandes [UNESP]; Chagas, Patrícia Da Silva Carlos [UNESP]; Kinoshita, Sérgio Koodi [UNESP] (Fundação Otorrinolaringologia, 2010)
INTRODUCTION: The military police are a population exposed to noise impact due to training with firearms. OBJECTIVE: To investigate the audiological profile of the military police in São Paulo state, and to correlate the age and duration of exposure and audiological findings. METHOD: In this study of case series, cross-sectional audiological evaluation was performed in 200 police officers being 169 (84.5%) were male and 31 (15.5%) females, aged between 25 and 45 years (mean 38.83 ± 5.05), average service time of 16.80 ± 6.27 years. RESULTS: The main complains were: tinnitus (n=52/26%), hearing loss (n=36/18%), ear fullness (n=24/12%) and autophonia (n=24/12%). Impedance were found in 100% of type A curves (JERGER, 1970), and recruitment was present in 20 (10%) cases. According to the results of audiometry, the data showed that 54 (27%) right ears and 56 (28%) left ears had hearing loss. The degree of loss with higher prevalence was 1 and 2 (MERLUZZI et al., 1979), 85 (42.5%) cases. There was significant correlation between age and exposure time with the worsening of audiometric thresholds in both ears. CONCLUSION: From the audiological data analysis was possible that the military police are a population that presents a risk to develop hearing loss. Thus, we see the need for implementation of hearing conservation program for the military police.

INTRODUÇÃO: Os policiais militares constituem uma população exposta a ruído de impacto devido aos treinamentoscom armas de fogo. OBJETIVO: Pesquisar o perfil audiológico em policiais militares do estado de São Paulo, e correlacionar à idade e o tempo de exposição com os achados audiológicos. MÉTODO: Neste estudo de série de casos, transversal, foi realizada avaliação audiológica em 200 policiais militares sendo 169 (84,5%) do gênero masculino e 31 (15,5%) do feminino, com idades entre 25 e 45 anos (média de 38,83±5,05), com média de tempo de serviço de 16,80±6,27 anos. RESULTADOS: As principais queixas apontadas foram: zumbido (n= 52 / 26%), disacusia (n=36 / 18%), plenitude auricular (n=24 / 12%) e autofonia (n=24 / 12%). Na imitanciometria foram encontradas 100% de curvas tipo A (JERGER, 1970), e houve presença de recrutamento em 20 (10%) casos. Segundo os resultados a audiometria tonal, os dados obtidos demonstraram que 54 (27%) orelhas direita e 56 (28%) orelhas esquerda apresentaram perda auditiva. Os graus de perda com maior ocorrência foram 1 e 2 (MERLUZZI et al., 1979), com 85 (42,5%) casos. Houve correlação significativa entre a idade e o tempo de exposição com a piora dos limiares audiométricos em ambas as orelhas. CONCLUSÃO: A partir da análise dos dados audiológicos foi possível verificar que os policiais militares são uma >população que apresenta risco para desenvolver a perda auditiva. Sendo assim, vemos a necessidade e implementação de programa de conservação auditiva para os policiais militares.
Audiology profile in the military police State of São Paulo
Keywords: polícia; ruído ocupacional; perda auditiva; police; occupational noise; hearing loss